(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2022)
Purpose: This study discusses perceived organizational support, job performance, and job crafting, and aims to determine the relationships between these variables with a mediated model. Methodology: In line with the purpose of the study, a literature review was first carried out and research hypotheses were developed based on both theoretical and empirical findings. The data required to test the hypotheses (222 data) were obtained from a company operating in the manufacturing sector in Konya (Turkey). Data were analyzed using the SPSS, AMOS, and PROCESS Macro software. Results: The analysis showed that perceived organizational support positively affects job crafting and job crafting positively affects job performance. Furthermore, job crafting was observed to have a mediating role in the effect of perceived organizational support on job performance. Conclusion: Perceived organizational support increases job performance both directly and indirectly. Therefore, the perception of support in the organization increases job crafting and ultimately job performance.